2005
DOI: 10.1021/ie0507124
|View full text |Cite
|
Sign up to set email alerts
|

The Hydration Behavior of Partially Sulfated Fluidized Bed Combustor Sorbent

Abstract: The efficiency of limestone sorbent utilization in fluidized bed combustors (FBCs) is low, because of incomplete sulfation of CaO. Hydration of the FBC ash can reactivate the partially sulfated sorbent, and the hydrated ash can be reinjected into the combustors as the SO2 sorbent. In this work, the rate of hydration, which is of primary importance in the reactivation process, is studied for FBC ash. The effects of major rate factors, temperature and particle size, are analyzed. At ambient temperature, the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Used sorbent reactivated with water for 1 min can reach 70% of the initial conversion of natural sorbent. There are many factors that affect the hydration of synthetic sorbents, but ultrasonic hydration could be a solution for reactivating this type of material [151], which was first proposed by Wang, Wu and Anthony [156] to enhance hydration in sulphated sorbent. However, direct water hydration is far from ideal due to the energy penalty caused by drying humid hydrated lime.…”
Section: Hydrationmentioning
confidence: 99%
“…Used sorbent reactivated with water for 1 min can reach 70% of the initial conversion of natural sorbent. There are many factors that affect the hydration of synthetic sorbents, but ultrasonic hydration could be a solution for reactivating this type of material [151], which was first proposed by Wang, Wu and Anthony [156] to enhance hydration in sulphated sorbent. However, direct water hydration is far from ideal due to the energy penalty caused by drying humid hydrated lime.…”
Section: Hydrationmentioning
confidence: 99%
“…2 show that the diffraction peaks of lime cannot be found after hydration for 6 h, and most of the lime in F0 is slaked at 1 h. The reason is that lime formed at about 800-900°C is highly reactive and can hydrate to Ca(OH) 2 in several hours [2,[29][30][31][32].…”
Section: Hydration Productsmentioning
confidence: 99%
“…It is possible that the highly exothermic hydration reaction leads to inner-pore expansion and inter-particle attrition, which favorably change the sorbent morphology. Reactivation of the deactivated CaO sorbents using hydration was previously reported for the purpose of CO 2 /SO 2 capture, and this is the first study showing that this reactivating method is also effective for this specific HCl capture scheme.…”
Section: Resultsmentioning
confidence: 57%
“…This drastic decrease in both surface area and pore volume can be used to explain the loss of chloridation reactivity after these two processes. When hydration is applied, an obvious increase in surface area and pore volume occurs to the deactivated CaO sorbent, which indicates that the closed pore structure is reopened by hydration. Combined with the result from TGA test 3, it can be inferred that the reactivating effect of hydration is likely a result of a physical process such as inter-particle attrition and inner-pore expansion rather than a chemical/crystal change from CaCO 3 -CaO to Ca(OH) 2 -CaO . On the basis of the experimental results and morphological analysis, it can be concluded that specially tailored precipitation (activation) and hydration (reactivation) are two effective methods that can improve or restore CaO sorbents’ morphological structure, which can subsequently lead to the enhanced HCl capture performance.…”
Section: Resultsmentioning
confidence: 93%